Hippocampus alters visual representation to encode new memory - Chenhui Liu; Zhen Liu; Kaiyuan Liu; Tianfu Zhang; Guangyu Wang; Hong Xie; Ji-Song Guan (Cell Reports)
Summary: Hippocampal-cortical interaction is crucial for episodic memory encoding and retaining, but when and how this interaction occurs remains elusive. Here, within the trace eyeblink conditioning paradigm, we found a neuronal ensemble in layer II of mouse visual cortex (VIS) that responded to the paired stimulus of light flash (cue, or conditioned stimulus [CS]) and air puff (unconditioned stimulus [US]), but not discrete stimuli, resembling an associative event during learning. This neuronal representation in VIS is dependent on the hippocampus and contributes to encoding the association. Optogenetic activation of hippocampus can promote the emerging representation to allow the association of separated cues. Mechanistically, fos+ engram cells, modulated by VIP+ neurons, are hubs of the association-activated ensemble in VIS. The hippocampus-modulated memory ensemble emerging in VIS at an early stage implicates the structural organization of the memory network to encode new memory.